2011
DOI: 10.5772/45703
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Aided Upper-Limb Rehabilitation Based on Motor Imagery EEG

Abstract: Stroke is a leading cause of disability worldwide. In this paper, a novel robot-assisted rehabilitation system based on motor imagery electroencephalography (EEG) is developed for regular training of neurological rehabilitation for upper limb stroke patients. Firstly, three-dimensional animation was used to guide the patient image the upper limb movement and EEG signals were acquired by EEG amplifier. Secondly, eigenvectors were extracted by harmonic wavelet transform (HWT) and linear discriminant analysis (LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
(28 reference statements)
0
23
0
Order By: Relevance
“…As shown in Figure 6a, Figure 6c (III). The amplitude ratio a1/a2 for a cycle T/2 could be represented as Equation (14), the logarithmic decrement δ is derived as Equation (15) from Equations (13) and (14). In this paper, δ (i = 3) are calculated in Equation (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 6a, Figure 6c (III). The amplitude ratio a1/a2 for a cycle T/2 could be represented as Equation (14), the logarithmic decrement δ is derived as Equation (15) from Equations (13) and (14). In this paper, δ (i = 3) are calculated in Equation (15).…”
Section: Methodsmentioning
confidence: 99%
“…Elements and actuators that are used in the devices have a profound effect on the compliance and lightness of the whole device. These include springs, pneumatic artificial muscles (PAMs) [1][2][3][4][5][6][7][8][9][10][11], magnetorheological (MR) dampers [12][13][14], shape memory alloys (SMAs) [15][16][17], soft pneumatic actuators (SPAs) [18], and dielectric elastomer actuators (DEAs) [19]. Research and development of these components and devices that employ them are widely conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The studies have also shown the existence of brain activity on the motor area recorded by electrodes positioned on the central areas of the cortex (C3, Cz, C4). When the subject performs an upper limb Motor Imagery (MI), the considered waves in the contra-lateral electrode concentrates more energy, while in the same side the energy is suppressed [7]- [10]. Others studies aiming at a better EEG resolution adopted a multi-electrode acquisition setup [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…No load is applied to the subjects' elbow. The desired trajectories are the same as in (18) and (19). The stimulating frequency and intensity of FES were fixed to 50 Hz and 20 mA, respectively.…”
Section: A Joint Movement Experiments Using Fesmentioning
confidence: 99%